Center and periphery: borderline cities and borderlines of cities - Čepaitienė, Rasa (Journal of Architecture and Urbanism, 2015)
Center and periphery: borderline cities and borderlines of cities.Journal of Architecture and Urbanism, 39(1), p. 1-2.